2018
DOI: 10.2507/ijsimm17(4)445
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Random Tagged Ore Flow through the Bunker in a Belt Conveying System

Abstract: Modelling the flow of a non-homogeneous ore is an important element needed to identify ore parameters for the purpose of ore processing control. The simulation model of the underground ore haulage system with the implemented function of estimating ore qualitative and quantitative parameters was built in the dedicated FlexSim simulation environment to address this issue. The transported ore is averaged in transfer and retention points, for instance in ore bunkers. This fact renders the modelling of ore flow ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…For the two-chute and one-chute bunker discharges, two values of mean retention time were incorporated into the FlexSim model-80 and 120 min, respectively. It was found that the one-chute bunker discharge variant of the FlexSim simulation complied well with the experimental time, while in the twochute variant the RFID tag flow times were shorter by about two hours (Bardzinski et al 2018). Within the experiment, some of the RFID tags were crushed or stuck to the mud and would therefore never reach the process plant.…”
Section: Experimental Verification Of the Modelmentioning
confidence: 56%
See 4 more Smart Citations
“…For the two-chute and one-chute bunker discharges, two values of mean retention time were incorporated into the FlexSim model-80 and 120 min, respectively. It was found that the one-chute bunker discharge variant of the FlexSim simulation complied well with the experimental time, while in the twochute variant the RFID tag flow times were shorter by about two hours (Bardzinski et al 2018). Within the experiment, some of the RFID tags were crushed or stuck to the mud and would therefore never reach the process plant.…”
Section: Experimental Verification Of the Modelmentioning
confidence: 56%
“…Any significant deviation from the plans requires the simulation to be restarted for new operating parameters of the system. The model can also be used to make economic decisions about further exploitation of each mining field, because it shows the contributions of each ore source to the total production of the metal, which was presented in previous studies (Bardzinski et al 2018(Bardzinski et al , 2019.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations